HUBUNGAN PENGETAHUAN TENTANG ANTENATAL CARE TERHADAP KUNJUNGAN KEMBALI MINAT IBU HAMIL TRIMESTER I DI PUSKESMAS TAPEN JOMBANG: The Relationship Of Knowledge About Antenatal Care To The Revisit Interest Of Pregnant Women's In Trimester I At Tapen Jombang Health Center - Nur Laila Faizah (LPPM - STIKES Pemkab Jombang, 2022)
Pregnancy is something that every married couple looks forward to, especially newly married couples. The government's efforts in tackling the maternal mortality rate are by focusing on the availability of maternal health services in the community. Knowledge of ANC is very important for pregnant women's interest in doing examinations. The sample in this study was all pregnant women who had at least made ANC visits in the Tapen health center area. The sampling technique used in this study is total sampling, namely the sampling technique taken from the entire population. Then analyze the data using the Chi-Square test. Based on the Independent Chi-Square test, the results were significant 0.01 < 0.05. It can be said that there is a relationship between knowledge about antenatal care and revisit interest in the first trimester of pregnant women at the Tapen Jombang Health Center.